Polish Anthropology Towards the End of the 20th Century – Directions and Trends of Development of its Social Functions - Drozdowski, Zbigniew (Anthropological Review, 1988)
Major trends of development of Polish anthropology were presented and its social functions with regard to the transformations of the Polish population.